A novel interplay between bacteria and metabolites in different early-stage lung cancer: an integrated microbiome and metabolome analysis - Zhai, Xiaoqian; Lin, Dongqi; Shen, Yi; Zhai, Ni; Yu, Fan; Zhang, Jiabi; Lin, Yiyun; Wang, Yuqing; Zhou, Qinghua; Zheng, Xi (Frontiers in Oncology, 2025)
BackgroundThe carcinogenesis mechanism of early-stage lung cancer (ESLC) remains unclear. Microbial dysbiosis is closely related to tumor development. This study aimed to analyze the relationship between microbiota dysbiosis in ESLC.MethodsWe investigated a total of 108 surgical specimens of lung nodules, including ground glass nodules (GGN) diagnosed as lung adenocarcinoma (n = 25), solid nodules (SN) diagnosed as lung adenocarcinoma (n = 27), lung squamous carcinoma (LUSC) presenting as solid nodules (n = 26), and benign pulmonary nodules (BPD) (n = 30) that were collected. 16S rDNA amplicon sequencing and non-targeted metabolomics analysis were performed in all of the specimens.ResultsWe found a significantly lower microbiota richness in SN than in the GGN and LUSC. Ralstonia may be an important flora promoting the development of early lung adenocarcinoma, while Feacalibacterium and Blautia play a protective role in the progression of GGN to SN. Akkermansia, Escherichia-shigella, and Klebsiella exhibited high abundance in early lung squamous carcinoma. Compared with BPD, the differential metabolites of both early adenocarcinomas (SN and GGN) are mainly involved in energy metabolic pathways, while early LUSC is mainly involved in glutathione metabolism, producing and maintaining high levels of intracellular redox homeostasis. A correlation analysis revealed that different microbiota in GGN may function in energy metabolism via N-acetyl-1-aspartylglutamic acid (NAAG) when compared to BPD, while creatine and N-acetylmethionine were the main relevant molecules for the function of differential microbiota in LUSC.ConclusionOur study identified that early-stage lung adenocarcinoma and squamous carcinoma differ in microbial composition and metabolic status. Ralstonia may be an important flora promoting the development of early lung adenocarcinoma, while Feacalibacterium and Blautia play a protective role in the progression of GGN to SN. Conversely, Akkermansia, Escherichia-shigella, and Klebsiella exhibited high abundance in early lung squamous carcinoma. The metabolites of both early adenocarcinomas (SN and GGN) are mainly involved in energy metabolic pathways, while early LUSC is mainly involved in glutathione metabolism. Our study provides new insights into the carcinogenesis of ESLC.